Muslim Mobilities: Geographies of Piety and Belonging in Tajik Dubai Business - Stephan-Emmrich, Manja (Anthropology of Islam, 2024)
A translocal ethnography about Tajik migrants’ engagement in projects of reform Islamic life in Dubai, the book maps Gulf migration onto larger geographies of Muslim mobility, piety and belonging across places in Eurasia, the Gulf, and wider Middle East. Spatializing the intersection of migration, work and Muslim piety, the book examines how formations of ethical subjectivity are closely tied to the multiple places that shape migrants’ travel itineraries and related experiences of dwelling there and crossing them. Situating these spatial biographies in broader transregional fields of Muslim mobility, connectedness and placemaking, the book explores why in the early 2000s young Tajik Muslims pursued spiritual, social and moral progress in the booming religious economy of Dubai’s fur coat business sector. The book’s spatial approach works threefold: With a focus on abroad, it interrogates the interplay of spatial perceptions of ‘the good elsewhere’ with migrants’ placemaking ‘there’. A second focus is on how multiplicity and flexibility of migrant situatedness (spatially, temporally, socially) in Persianate, Russophone and Arab culturescapes shape mobile pious subjectivities and cosmopolitan belongings. The book also develops a situated Tajik perspective on Gulf migration, that grounds in circulating spatial imaginaries, Muslim knowledge repertories, as well as in individual travel modes, paths and migrant experiences resulting from precarious livelihoods and discriminating migrant regimes. Linking anthropology with new area studies approaches, this book seeks to enhance multidisciplinary scholarship about the complex relation between religion, migration and mobile subjectivity in both Central Asian and Gulf studies and in the anthropology of Islam.